Theoretical and experimental investigations of zinc oxide nanostructures as photoelectrode for solar cell application - Fatin Farisha Alia, Azmi (2023)
Scientists have been interested in solar cells for many years due to its ability to generate electrical energy from sunlight. One of the promising recent developments in this field is the quantum dots solar cell (QDSC) that can potentially replace dye sensitized solar cell (DSSC) due to their relatively simpler device structure and similarity. In QDSCs, the photovoltaic (PV) effect occurs at the interface between a redox electrolyte and the quantum dot (QD) conjugated wide bandgap metal oxide semiconductor (MOS), instead of dye molecules. QDs also have several advantages over organic dyes, including better electrical and optical properties due to several reasons, which are: (i) QD size-dependent tuneable bandgap, (ii) larger absorption cross-section, and (iii) ability to produce multiple excitons generation (MEG) from the absorption of a single-photon. In recent years, researchers have been focusing only on fluorophores and electrolytes in solar cells rather than on the photoelectrode. This research aims to (i) fabricate ZnO nanoparticles (NPs) using the thermal evaporation (TE) method and study their opto-electronic properties, (ii) study the effect of evaporation cycles to the properties of fabricated ZnO NPs, and (iii) build and validate realistic cluster models of ZnO NPs using ab-initio density functional theory (DFT) calculations. The TE pressure of 5 × 10-4 Torr and 5 × 10-5 Torr exhibited increments in: (i) bandgap of 2.58 eV and 2.80 eV, and (ii) PV efficiency of device ZnO/PbS/Carboxymethyl cellulose and polyvinyl alcohol (CMC-PVA) of 0.00181% and 0.99%, respectively. The different evaporation cycles i.e., one-, two-, and three-evaporation cycles caused variations in the size range of distribution of ZnO nanosphere (decreasing upon increment of evaporation cycles), and bandgap of ZnO nanosphere (increasing upon increment of evaporation cycles). The structural geometries of ZnO were identified viz., (ZnO)3, (ZnO)5, (ZnO)6, (ZnO)16, (ZnO)24, and (ZnO)30 with the size of 1.788 nm, 2.459 nm, 2.651 nm, 4.997 nm, 6.543 nm, and 7.529 nm respectively. The energy level alignment which involves the lowest occupied molecular orbitals of CdSe (LUMOCdSe) and (ZnO)30 is hypothesized to be able to satisfy the demand of i.e., (i) electron injection from CdSe to the ZnO (LUMOCdSe > LUMOZnO), and (iii) efficient electron transport (LUMOZnO < LUMOCdSe). The first excitonic peak of (ZnO)30 is in a good agreement with that of the ZnO thin film, thus it is hypothesized that the (ZnO)30 realistic cluster could be fabricated. In conclusion, the (ZnO)30 nano-sphere could be fabricated using TE with the fabrication pressure of 5 × 10-5 Torr and three-evaporation cycle for a better adsorption of thin film.